Pengaruh Target Kerja, Lingkungan Kerja Terhadap Turnover Intention Karyawan Unit Wooden Houseware Di Pt. Inspira Furnexindo - Sherly Rosita Putri Sulaiman; Maulidyah Amalina Rizqi (Universitas Veteran Bangun Nusantara, 2023)
Based on research at PT. Inspira Furnexindo is used to determine differences in work levels and work environment on turnover intention variables from other variables. From the reference to the results of the F-test value on the calculation of turnover intention, at PT. Inspira Furnexindo, the results obtained and several possible results are obtained from the work target variables and work environment, where the results obtained are lower with a significant level value of Sig. (0.046) < 0.05, with the calculated F value being (3.187) > F table with value (3.1065). Based on the explanation above, the work target variable (x1) and the work environment variable (x2) are obtained, the results obtained are in the form of simultaneous results that significantly influence turnover intention (Y). For the value of the results of the hypothesis testing data from this study, the results obtained with the work target variable with the Work Environment partially have no effect on turnover intention at PT. Inspira Furnexindo. However, with the existence of a joint work target with a good work environment variable, it can create working conditions with a good level of risk at a low level of turnover intention in a corporate environment.